2019
DOI: 10.2991/chi.d.190310.001
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic Stem Cell Transplantation for FLT3-Mutated Acute Myeloid Leukemia: In vivo T-Cell Depletion and Posttransplant Sorafenib Maintenance Improve Survival. A Retrospective Acute Leukemia Working Party-European Society for Blood and Marrow Transplant Study

Abstract: Acute myeloid leukemia (AML) with FLT3-mutation carries a poor prognosis, and allogeneic stem cell transplantation (allo-SCT) is recommended at first complete remission (CR1). We assessed 462 adults (median age 50 years) with FLT3-mutated AML allografted between 2010 and 2015 from a matched related (40%), unrelated (49%), or haploidentical donor (11%). The median follow-up of alive patients was 39 months. Day-100 acute graft versus host disease (GVHD) grades II-IV and III-IV were encountered in 26% and 9%, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 56 publications
1
41
0
Order By: Relevance
“…This will likely increase the predictive value of pretransplant MRD status on relapse risk and OS above what has been observed with MRD positivity as currently ascertained in the EBMT registry database. Further, having these data in the registry will also benefit to study assessing the impact of prophylactic intervention such as posttransplant immunosuppression discontinuation, donor lymphocyte infusion, or targeted low-intensity therapies on leukemia progression [34][35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…This will likely increase the predictive value of pretransplant MRD status on relapse risk and OS above what has been observed with MRD positivity as currently ascertained in the EBMT registry database. Further, having these data in the registry will also benefit to study assessing the impact of prophylactic intervention such as posttransplant immunosuppression discontinuation, donor lymphocyte infusion, or targeted low-intensity therapies on leukemia progression [34][35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the outcome of haplo-SCT for MRD-FC-positive patients was comparable with that demonstrated for subjects with pre-transplant MRD-FC-negativity [17]. In the light of the recent findings and when confirmed in prospective studies, it seems reasonable to consider FLT3 inhibitor as a part of induction therapy and post-transplant maintenance [18,19]. A double-blind randomized study showed that the addition of midostaurin to standard chemotherapy significantly improved overall and event-free survival in FLT3positive AML patients; however, midostaurin was not beneficial as maintenance treatment after transplantation [18].…”
Section: Discussionmentioning
confidence: 52%
“…Sorafenib was the first TKI studied in the setting of posttransplant maintenance therapy in AML with FLT3-ITD mutation. It showed benefit in survival and improvement of outcomes in a phase I study, several retrospective studies and two randomized studies (80)(81)(82)(83)(84)(85)(86)104). Chen and colleagues (80) reported the results of the first phase I trial on sorafenib after transplant in 22 patients with FLT3 mutated AML.…”
Section: Flt3 Inhibitors As Maintenance Therapymentioning
confidence: 99%
“…A recent update of this study after a median follow-up of 40 months further demonstrated promising long-term outcomes with sorafenib maintenance with 2-year PFS and OS of 73% and 80%, respectively. Recently Bazarbachi and colleagues (85) reported the results of European Society for Blood and Marrow Transplantation (EBMT) registry-based study on 462 allo-grafted FLT3-mutated AML patients (FLT3-ITD-95%) over a median follow-up of 39 months for surviving patients. Among these patients, 28 received posttransplant sorafenib maintenance as prophylactic (n = 19) or preemptive therapy (n = 9), started at a median of 55 days posttransplant (range 1-173 days) and a median dose of 800 mg/day (range 200-800 mg/day).…”
Section: Flt3 Inhibitors As Maintenance Therapymentioning
confidence: 99%